The Use of Donor with Renal Failure in Cadaver and One-Year Outcome. (July 2018) - Elgin, Ersin; Yildiz, Abdülmecit; Oruç, Ayşegül; Çoşkun, Burhan; Kaygusuz, Onur; Ersoy, Alparslan; Keskin, Sahriye; Vuruşkan, Hakan; Selimoğlu, Kerem; Dündar, Halit Ziya
Abstract : Objective: The use of transplants from donors with acute kidney injury may negatively affect the outcome after renal transplantation. In this study, we evaluated one-year graft survival and renal functions in patients who transplanted from deceased donor with acute kidney injury. Method: Retrospective study, over a period of 4 years between 2011 and 2015 were carried out. A total of 161 deceased donor, of which, sixty-three donor (Group A) with acute kidney injury whose former renal functions were normal and ninety-eight standard donor (Group B)not carry any expanded criteria were included to the study. Results: In both groups, mean donor age were 44 ± 14, and 48 ± 16 respectively and not different between groups (p=0, 103).In group B, male sex ratio was significantly higher(%73vs%49, p=0, 003) Cold ischemia time(>12 hour, %66 in group A vs %69 in group B, p=0, 731) was not different. Antigen mismatch were not different between groups (2, 3±1, 1in group A vs 2, 2±0, 8 in group B p=0, 592) One year death ratio and creatinine levels were not different between groups ( 11%in group A vs 17% in group B, p=0, 323) (1, 46 ±0, 9 in group A vs 1, 45± 0, 8 in group B, p=0, 95). Conclusion: These results suggest that Despite Acute kidney injury in donors, one-year outcome is not different and donor with acute kidney injury should not be excluded.